Investigation of Blood Parasites of Birds and Rodents at Tasik Abrar Universiti Sains Islam Malaysia - Aimi Nurnajihah Shahrul Kamil; Farah Shafawati Mohd Taib; Mohd Sanusi Mohamaed; Mohamad Arif Iskandar Abdul Wahab; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page:68-71